The role of the major histocompatibility complex and the Leukocyte receptor complex genes in susceptibility to tuberculosis in a South African population - Salie, Muneeb (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.